Research methods for educational dialogue - Kershner, Ruth; Hennessy, Sara; Wegerif, Rupert, 1959-; Ahmed, Ayesha (London, England : Zed Books, 2020)
"Research Methods for Educational Dialogue provides an overview of the range of possibilities for researching various forms of educational dialogue, underpinned by a coherent theoretical foundation. The authors, Kershner, Hennessy, Wegerif and Ahmed offer an integrated understanding of different methodological approaches in this fast-growing area of education. The book includes critical discussion of a variety of methods for investigating the characteristics and quality of dialogues for individuals and groups of participants in different educational contexts. These include student-student, teacher-student and wider professional dialogues, conducted face-to-face, online or mediated by classroom technologies. The authors argue for the integration of ethical and methodological principles, and consider the potential for innovative research methods that are dialogic in themselves. Including chapter commentaries from invited experts in the field, authentic research examples and a glossary of terms, this is essential reading for anyone looking to research in the area of educational dialogue."--Publisher's description.
Introduction -- Foundations for research on educational dialogue -- Orientations and ground rules: a framework for researching educational dialogue -- Methodological developments in research on educational dialogue: mapping the field -- Dialogic participation and outcomes: evaluation and assessment -- Analytical coding schemes for classroom dialogue -- Methods for researching technology-mediated dialogue -- Researching online dialogues: introducing the 'chiasm' methodology -- Dialogue, participation and social relationships -- Researching dialogue in educational decision making -- Conclusion.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Communication in education; Communication in education -- Research -- Methodology; Research methods: general; Electronic books